Introduction and Training of IT Entrepreneurs for the People of Kalidoni RT District. 34 RW.07 - Serly Oktarina; Ubaidillah Ubaidillah; Hadi Syaputra; Siti Zubaidah; Yuwinti Nearti; Hermansyah Hermansyah; Zahra Ahmadi (Asosiasi Profesi Multimedia Indonesia, 2024)
The aims of this service are (1) to improve the quality, insight and awareness of teenagers about the importance of science and technology skills in competing in the era of globalization and being able to utilize technology in entrepreneurship so that their standard of living changes for the better. (2) to provide understanding for the community related to Entrepreneurship. The methods used are (1) Theoretical basic knowledge of computer practice to support computer training. (2) Evaluation of theory & practice test. The results show that (1) Participants understand the importance of non-formal education guidance services and instill social values in the youth who are the target of the activity. (2) It is the best solution to overcome the problem of a lack of knowledge of science and technology in society. It can be concluded that the low quality of human resources has become a polemic in the community, therefore, with computer training, participants are expected to be able to apply it well in the world of work and education and take advantage of science and technology skills in online entrepreneurship.